PENGARUH MODEL PEMBELAJARAN MISSOURI MATHEMATICS PROJECT TERHADAP HASIL BELAJAR SISWA PADA MATERI SPLTV KELAS X MIPA SMA GKST 1 TENTENA: The Influence Of The Missouri MA The Matics Project Learning Model On Student Learning Out Cames In The STVLE For Class X MIPA SMA GKST 1 Tentena - Maladjadji, Joice Celcea Gloria; M, Bakri (Universitas Tadulako, 2024)
This study aims to determine whether or not there is a significant influence between learning models on the learning outcomes of students in class X MIPA SMA GKST 1 Tentena. The research method used in this study is an experimental method that aims to see the causal relationship. The population of this study were all X MIPA students of SMA GKST 1 Tentena as many as 92 people consisting of 3 classes. The sampling technique used simple random sampling. The sample in this study consisted of 60 students in the 2023/2024 school year, 30 students in the experimental class and 30 students in the control class. The results of data analysis that have been obtained, the average score of students in the experimental class is 88.77 with a standard deviation of 8.199, while the average score of students in the control class is 84.47 with a standard deviation of 7.468. The results of hypothesis testing using the independent sample t-test showed that there was a significant effect of the Missouri Mathematics Project learning model on the learning outcomes of GKST 1 Tentena High School students